2019
DOI: 10.1177/2049463719866877
|View full text |Cite
|
Sign up to set email alerts
|

Time course of attentional bias to painful facial expressions and the moderating role of attentional control: an eye-tracking study

Abstract: Introduction: This study investigated the time course of attention to pain and examined the moderating effect of attentional control in the relationship between pain catastrophizing and attentional bias in chronic pain patients. Methods: A total of 28 patients with chronic pain and 29 pain-free individuals observed pictures of pain, happy and neutral facial expressions while their gaze behaviour was recorded. Pain intensity and duration, anxiety, depression, stress, attentional control and pain catastrophizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 64 publications
(95 reference statements)
4
34
0
1
Order By: Relevance
“…Furthermore, post-hoc analyses showed that this was not related to self-reported ability to focus attention, but rather the ability to shift attention. Only one recent study has investigated the moderating role of attentional control in adults with chronic pain between attentional bias and pain catastrophizing 19 . Mazidi et al 19 used a dot-probe task with eye-tracking (with 1500msec presentation).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, post-hoc analyses showed that this was not related to self-reported ability to focus attention, but rather the ability to shift attention. Only one recent study has investigated the moderating role of attentional control in adults with chronic pain between attentional bias and pain catastrophizing 19 . Mazidi et al 19 used a dot-probe task with eye-tracking (with 1500msec presentation).…”
Section: Discussionmentioning
confidence: 99%
“…Only one recent study has investigated the moderating role of attentional control in adults with chronic pain between attentional bias and pain catastrophizing 19 . Mazidi et al 19 used a dot-probe task with eye-tracking (with 1500msec presentation). They found a general pattern of vigilance-avoidance amongst people with and without chronic pain and a moderation effect of attentional control in the relationship between pain catastrophizing and attention to happy faces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations